Tetanus in unvaccinated persons: A review of case reports - E. I. Komarovskaya; O. V. Proskurina (Биопрепараты: Профилактика, диагностика, лечение, 2025)
INTRODUCTION. Cases of tetanus are registered annually throughout the world, mainly in unimmunised or incompletely immunised populations. Analysis of tetanus cases and identification of the reasons for non-vaccination, including refusal to vaccinate, are important for drawing the attention of health professionals to this issue.AIM. This study aimed to review case reports of tetanus in unvaccinated or partially vaccinated individuals, analyse reasons for non-vaccination, and identify problems associated with preventive vaccination against tetanus.DISCUSSION. According to epidemiological data, cases of tetanus are recorded every year in almost every country in the world. In 2023, the World Health Organisation (WHO) reported 21,830 cases of tetanus worldwide, and the Russian Federation reported 8 tetanus patients, including children. The main issue with diagnosing tetanus lies in the lack of reliable laboratory tests for confirming tetanus. Tetanus-specific therapy with tetanus antitoxin (equine) is associated with the risk of allergic reactions. Traditionally, tetanus is considered an infection that develops only in patients with deep and soil-contaminated wounds. However, unvaccinated or partially vaccinated individuals are at high risk of tetanus, even with minor wounds. This study involved an analysis of case reports of tetanus (13 cases) in unvaccinated or partially vaccinated individuals with minor wounds or wounds minimally contaminated with soil. In all the paediatric tetanus cases discussed in this article, the parents had not vaccinated their children for religious and/or personal reasons. The analysis of case reports of tetanus in adults showed that the patients had not taken their wounds seriously and had not sought medical help before the onset of the disease.CONCLUSIONS. The concerning incidence of tetanus is attributed to insufficient public awareness of the dangers of the disease and the rising number of people refusing vaccines. Health professionals, public organisations, and religious communities should work together to promote vaccination and improve health education. This will enhance public confidence in vaccination, increase preventive vaccination coverage, and reduce the incidence of tetanus.